Analysis On Nuclear Non-Proliferation Aspect Based On Transuranium Production Of Several Different Reactor Types - SAPUTRA (NIM : 10209027); Pembimbing : Dr. Eng. Sidik Permana, GEBY
Analysis on Nuclear Non-proliferation Aspect Based on Transuranium Production of several different reactor types has been done in this final project. Production of analyzed transuranium consists of plutonium and minor actinide such as Neptunium (Np), Americium (Am), and Curium (Cm). Several types of reactor used in these analyses consist of Light Water Reactor (LWR), which is from Pressurized Water Reactor (PWR) and Boiling Water Reactor (BWR), type of CANDU, and Liquid Metal and Fast Breeder Reactor (LMFBR). The method used in this experiment is a simulation method using syntax ORIGEN 2.2. In the early step of the simulation is to compare all of the four reactors by simulating from a standard code from each reactor simulation. Then, the further experiment is done at PWR reactor by giving two variations in both input of simulation program. The variations done are to increase the value of BU by same enrichment and to compare the result and the variation of BU and increasing fuel enrichment. The value of BU is 33GWd/t, 45GWd/t, and 60 GWd/t. The percentage of uranium (U-235) enrichment used is 3% to 9%. The data shows the changes of Kinf value, composition of MA (Np, Am, Cm), and composition of plutonium and uranium. Production of plutonium and minor actinide could be used as one of parameter to analyze a nuclear non-proliferation aspect. Composition of isotope plutonium could be a material controller to analyze plutonium non-proliferation aspect and could also be a utilization of recycled minor actinide.